Cathodoluminescence and its Application in the Planetary Sciences - Gucsik, Arnold. (Springer, 2017)
This book provides an overview of cathodoluminescence properties of the planetary materials. It is unique in that it is the first book of its kind presenting new important data on cathodolumiescence spectrocopy and microscopy on samples of impactites, meteorites, shock recovery experiences and Interplanetary Dust Particles. Each chapter is written by a well-known specialist and covers new fields such as shock-induced microdeformations in minerals, astrobiology and the cosmochemistry of meteorites.